Julia 1.0 Programming Cookbook : Over 100 numerical and distributed computing recipes for your daily data science workﬂow /: Over 100 numerical and distributed computing recipes for your daily data science workﬂow. (2018) - Kamiński, Bogumił; Szufel, Przemysław
No abstract available